GENERAL EQUILIBRIUM AND ECONOMIC EFFICIENCY IN ECONOMY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article is about terms, general equilibrium and economic efficiency which are fundamental concepts in economics that play a crucial role in shaping the functioning of an economy. These concepts are closely intertwined and are essential for ensuring optimal resource allocation and overall welfare in a market system.